2019
DOI: 10.1093/pm/pnz012
|View full text |Cite
|
Sign up to set email alerts
|

Unique Characteristics of the Dorsal Root Ganglion as a Target for Neuromodulation

Abstract: Objective The dorsal root ganglion (DRG) is a novel target for neuromodulation, and DRG stimulation is proving to be a viable option in the treatment of chronic intractable neuropathic pain. Although the overall principle of conventional spinal cord stimulation (SCS) and DRG stimulation—in which an electric field is applied to a neural target with the intent of affecting neural pathways to decrease pain perception—is similar, there are significant differences in the anatomy and physiology of the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
159
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(162 citation statements)
references
References 92 publications
3
159
0
Order By: Relevance
“…At the sensory ganglia resides the soma of nociceptors and other somesthetic neurons as well as specialized glial cells, the satellite glial cells (SGC). Besides the important role in metabolic support, events at DRG are known to participate in the development of pathological pain (Devor, 1999;Esposito et al, 2019). Primary afferent neurons at the DRG do not interact with one another through synaptic contact.…”
Section: Introductionmentioning
confidence: 99%
“…At the sensory ganglia resides the soma of nociceptors and other somesthetic neurons as well as specialized glial cells, the satellite glial cells (SGC). Besides the important role in metabolic support, events at DRG are known to participate in the development of pathological pain (Devor, 1999;Esposito et al, 2019). Primary afferent neurons at the DRG do not interact with one another through synaptic contact.…”
Section: Introductionmentioning
confidence: 99%
“…The postoperative PHN incidence rate is 4.55%, and this is similar to the previous reports both at home and abroad. 10 In summary, CT-guided puncture of the costal transverse process in the dorsal root ganglion with pulsed radiofrequency treatment of T1-T3 herpes zoster neuralgia demonstrated a high success rate and is considered to be safe and effective. This study provides a new technique guide for CT-guided puncture technology and also provides an effective reference for clinical treatment of patients with herpes zoster involving T1-T3 areas.…”
Section: Discussionmentioning
confidence: 97%
“…9 Recent clinical studies have revealed that pulsed radiofrequency treatment of dorsal root ganglion in managing herpes zoster neuralgia has achieved ideal therapeutic effects. [10][11][12] CT-guided dorsal root ganglion puncture is considered safe and accurate, and so it is widely used for treating PHN clinically, 13,14 However, it is worth mentioning that when herpes zoster is involved in the upper thoracic segment, especially in the area of dorsal root ganglion of T1-T3, CT-guided puncture often remains difficult due to blockage of the lamina, transverse process, and ribs. This not only prolongs the operation time, but also increases the patient's pain, making it difficult to obtain the expected operation results.…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple changes in gene expression in DRG under pain condition, encompassing a large number of distinct family members including neuropeptides, receptors, ion channels, signal transduction molecules, synaptic vesicle proteins, and others [41,42]. The functional consequence of these changes is sensitization and hyperexcitability of DRG neurons, which then leads to persistent pain [18]. Moreover, the DRG is consistently locating at the intervertebral neural foramina within a capsule which is an easily accessible target.…”
Section: Intervertebral Foramen Injection Is An Appliable Treatment Amentioning
confidence: 99%
“…Consequently, the abovementioned drug systemic administration modality will inevitably result in a number of adverse events and blur the action site of the plerixafor. Giving that the dorsal root ganglion (DRG) containing bodies of primary sensory neurons which may generate abnormal spontaneous discharges and become an important source of hyperexcitability and increased nociceptive signaling, the intervertebral foramen injection aiming at delivering drugs onto the DRG might be an appropriate alternative approach for drug delivery [16][17][18].…”
Section: Introductionmentioning
confidence: 99%